Smart Room Design as a Concrete Step Towards a Sustainable Smart Campus at the Institut Teknologi Sumatra - Sabhan Kanata; Sabar Sabar; Amrina Mustaqim; Gde Komang Atmajaya; Muhammad Rizky Hikmatullah; Muhammad Asrofi; Asmar Asmar (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2023)
Institut Teknologi Sumatera (ITERA) is one of the new PTN campuses in Indonesia. As a campus that carries the smart-campus motto, ITERA will continue to create smart services, including saving electrical energy. One of the programs to support a sustainable campus is innovation in electrical energy management so that electrical energy efficiency can be maximized. The ITERA smart-room product called SMARTERA is one of the campus's tangible manifestations to control electrical equipment using Internet-based intelligent control of Things (IoT). The initial stage in this research is automatic control of the two most widely used electrical equipment in the campus environment, namely lights and air conditioning (AC)